High prevalence of BRAFV600E in patients with cholestasis, sclerosing cholangitis or liver fibrosis secondary to Langerhans cell histiocytosis. Issue 7 (15th May 2021) - Carrere, Xiomara; Pinto, Nicolas; Gene Olaciregui, Nagore; Galluzzo, Laura; Rossetti, Estefania; Celis Passini, Veronica; Salvador Marcos, Noelia; Chantada, Guillermo; Braier, Jorge; Lavarino, Cinzia; Felizzia, Guido
Abstract: Targeted therapies with MAPK inhibitors have proven to modulate the clinical manifestations of patients with Langerhans cell histiocytosis (LCH). We explored the presence of BRAF V600E mutation in our cohort of patients with LCH and cholestasis, sclerosing cholangitis, or liver fibrosis that presented resistance to chemotherapy. The BRAF V600E mutation was detected either in the diagnosis (skin and bone) or liver biopsy in our cohort of 13 patients. Thus, we observed a high incidence of BRAF V600E mutation in 100% either in diagnostic biopsy (skin and bone) or liver biopsy in patients with progressive liver disease, sequela, or liver transplant requirement.